The state of contemporary molecular diagnostics of colorectal cancer - Żelazowski, Maciej J.; Bednarek, Andrzej K. (Contemporary Oncology/Współczesna Onkologia, 2011)
The most important methods of colorectal cancer prognosis are TNM and Dukes staging, which have remained basic CRC classification systems for many years. In view of increasing incidence of this type of cancer, scientists are still looking for more advanced methods, allowing for early detection and better classification aimed toward personalized therapy. Some of such methods (diagnostic markers) could be implemented for screening of groups at risk. In parallel, new prognostic markers are also sought, which compared with the standard markers (invasion of cancer cells to lymph nodes, tumour size or histological malignancy) could have a greater ability to determine the prognosis of patients with colorectal cancer and facilitate the selection of optimal chemotherapy. In this article we will focus on the state and prospects of modern molecular diagnostics of colorectal cancer.